Analisis Faktor yang Memengaruhi Keluhan Low Back Pain pada Perawat di Rumah Sakit Umum Bunda Lhokseumawe - Putri Aswina; Tri Niswati Utami; Tri Niswati Maryanti (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Abstract-The prevalence of low back pain in nurses at Bunda General Hospital Lhokseumawe is 42 nurses. This study aims to analyze the factors that influence the emergence of low back pain in nurses. This research is a quantitative study with a cross-sectional study design which was carried out at Bunda General Hospital Lhokseumawe which took place from October to November 2020. The study population was all nurses at Bunda General Hospital Lhokseumawe, namely 42 people. The technique used is total sampling. Survey data were analyzed using the Chi Square test and logistic regression. The results of the univariate study showed that of the 42 respondents, most of the respondents were aged 36-45 years (59.52%), were female (69.05%), had a D3 degree in Nursing education (71.43%). Bivariate results showed that there was an effect of revetitive motion (p=0.013), awkward postures (p=0.000), contact stresses (p=0.006) on the incidence of low back pain in nurses. The multivariate results showed that the variable that had the most influence on the occurrence of low back pain in nurses at Bunda Lhokseumawe General Hospital was revetitive motion (p=0.031). Suggestions in this study are that it is hoped that hospitals can innovate administrative controls by providing educational posters affixed to areas that are often passed by nurses regarding ergonomic work attitudes that can prevent low back pain. Keywords: Repetitive Movement, Awkward Posture, Stress Contract, Low Back Pain